The Impact of COVID-19 on Villages: Results from a National Survey. Issue 4 (19th May 2022) - Galucia, Natalie; Morrow-Howell, Nancy; Sun, Peter; Meyer, Tanner; Li, Ying
ABSTRACT: Villages are consumer-driven organizations that promote aging-in-place. This study documents the effects of the COVID-19 pandemic on Villages and explores variation in response by age of the organization, size of the membership, staffing model, and geographic location. In summer, 2020, we distributed an online survey to executive administrators of 286 Villages in the network. During the pandemic, over 75% of Villages were seen as more or equally valuable for members. Seventy-seven percent of Villages offered virtual socialization events. Most Villages reported a decrease in service requests, given reductions in need for transportation. New services of food and medication delivery were initiated. There is much variation between organizations, but findings suggest that Villages that are older, have more members, and bigger budgets had more capacity and cushion; and although they took a negative hit in income and participation, it was a smaller hit proportionately, compared to younger and smaller Villages. Villages have demonstrated adaptability and creativity. They kept their operations running, provided services, and offered social connection. Vulnerabilities have been exposed: memberships have dropped for many and some members have not been able to participate as before the pandemic. Many lessons learned can help future developments of the Village model.